(untitled) (Communications in Computational Physics, 2020)
The goals of this study were to examine factors influencing Q inversion and to provide references for practical application. Three different methods for inverting Q values with VSP data were explored, including centroid frequency shift (CFS), spectral ratio (SR), and amplitude attenuation (AA). Comparison between the CFS and the other two methods was conducted on frequency band widths and low attenuation, wavefield components, interface interference, and thin layers. Results from several sets of VSP modeling data indicated that the CFS method is more stable and accurate for dealing with thin and high Q layers. Frequency band width, especially the presence of high frequencies, influences the inversion effect of all three methods. The wider the band, the better the results. Q inversion from downgoing wavefield was very similar to that of the upgoing wavefield. The CFS method had fewer outliers or skip values from the full wavefield than the other two methods. Moreover, the applications to Q inversion for the set of field VSP data demonstrated that the Q curves from the CFS method coincided with the geological interpretations better than the Q curves of the other methods. Meanwhile, inverse Q filtering shifted the frequency component from 25 Hz to 35 Hz. The results demonstrated that the Q curve is more sensitive to geological horizons than velocity.